“Literature on the Edge”: Austro-Modernism of the Long War - Bollobás, Enikő (Hungarian Journal of English and American Studies, 2021)
Book review:Perloff, Marjorie. Edge of Irony: Modernism in the Shadow of the Habsburg Empire. Chicago: U of Chicago P, 2016. 204 pages. ISBN-13: 978-0-226-05442-1. Hb. $23.98.